Problems of the Continuation of Medieval Manufacturing Traditions in Modern Shoemaking Based on Archaeological Finds in Szczecin - Kowalska, Anna B. (Analecta Archaeologica Ressoviensia, 2024)
Research into modern leather footwear has only recently become a part of archaeology. In the case of Szczecin, a town on the Baltic coast in Western Pomerania, no comprehensive study on these types of finds has yet been compiled. This article discusses footwear dating to the period between the 16th and 19th centuries which has been uncovered during archaeological excavations in the Old Town in Szczecin, the issue of continuation of medieval shoemaking traditions as well as the issues of the methodology of studies and nomenclature used in Polish literature on the subject.